Changes in core temperature and hydration status during a competitive football match played in cool conditions. Issue 15 (10th November 2011) - Watson, P; Clark, M; Bryan, J; Maughan, R J
Abstract : Football is played throughout the world in a wide range of environmental conditions. Thermal responses to match play in temperate and warm conditions have been widely reported, but there little published work that has quantified changes in core temperature and hydration status when football is played in cool conditions. Fifteen male university football players (age 20 ± 1 y, height 1.81 ± 0.06 m, body mass 79.7 ± 9.5 kg) took part in a competitive match in cool conditions (6.5 ± 0.8°C, 66 ± 4% relative humidity). Core temperature (Tc) was measured using an ingestible telemetric sensor (HQ Inc. Florida, USA). Sweat losses were assessed from the change in body mass after correction for the volume of fluid consumed. Tc prior to the start of the match was 37.3±0.3°C. T of the starting players increased as the match progressed (P < 0.05), with values of 39.0±0.4°C and 39.1±0.4°C recorded at half time and full time respectively. The highest individual Tc was 39.6°C. The Tc of the reserve players (n=5) increased above resting values after the warm up (P < 0.05), but decreased as the match progressed. While this was not statistically different from prematch values, two reserves did fall below 37.0°C. Body mass losses of starting players were 1.04±0.35 kg (range 0.57–1.48 kg). Fluid intake during the match was 0.72±0.34 l. When corrected for the ingestion of fluid, and any urine output, the estimated sweat losses were 1.53±0.41 l (range 0.75–2.00 l), which corresponds to a sweat rate of 1.0±0.3 l/h (range 0.5–1.3 l/h). The present study suggests that players involved in competitive football matches played in cool conditions exhibit similar thermoregulatory and hydration responses to those reported during match play in more temperate conditions. As competitive football is played in colder conditions than those experienced in this study, further research into the physiological response of players to these conditions is warranted.